AKOMODASI KULTURAL DALAM RESOLUSI KONFLIK BERNUANSA AGAMA DI INDONESIA - Zaenuddin Hudi Prasojo; Mustaqim Pabbajah (Aqlam: Journal of Islam and Plurality, 2020)
Abstract: Ethnic and religious diversity in Indonesia have become not only a wealth but in the same time also a threat to the country. They have also become the sources of cultural diversity as cultural assets that need attention. In fact, these cultural assets have potentials in the emergence of social and religious conflicts. This article suggests important findings carrying three main issues in looking at conflicts in the name of religion. With qualitative data analysis, the three main issues are collaborated. First, the conflict that took place in Indonesia tends to occur in three forms including; communal conflicts, sectarian conflicts and political installation conflicts. Second, conflict in the name of religion is triggered by several factors including lacking of understanding of the cultural, ethnic and religious diversities in Indonesia. Third, cultural accommodation by looking at the potential of local wisdom has been evidence to offer useful, needed alternatives in solving conflicts that occur in the community. This work recommends that it is necessary to deepen and disseminate all parties in empowering the potential of local culture in Indonesia. Keyword: Accomodation, Culture, Religion, Conflict Resolution Abstrak: Keragaman etnis dan agama di Indonesia merupakan kekayaan sekaligus sebagai ancaman bagi negara ini. Keragaman etnis dan agama menghasilkan keragaman budaya yang merupakan aset kultural serta perlu mendapatkan perhatian. Aset kultural tersebut berpotensi besar dalam kemunculan konflik sosial maupun agama. Artikel ini menawarkan temuan penting mengenai tiga isu utama dalam melihat konflik atas nama agama. Dengan analisis data kualitatif, ketiga isu utama tersebut dielaborasi. Pertama, konflik yang berlangsung di Indonesia cenderung diperlihatkan dalam tiga bentuk antara lain: konflik komunal, konflik sektarian, dan konflik eskalasi politik. Kedua, faktor konflik agama dipicu beberapa faktor yang meliputi masih minimnya pemahaman realitas keragaman suku, etnis, dan agama di Indonesia. Ketiga, akomodasi kultural dengan melihat potensi kearifan lokal telah mampu dijadikan sebagai perangkat penyelesaian permasalahan konflik yang terjadi di tengah masyarakat. Rekomendasi artikel ini adalah diperlukan pendalaman dan sosialisasi semua pihak dalam memberdayakan potensi budaya lokal di Indonesia. Keyword: Akomodasi, Kultural, Agama, dan Resolusi Konflik